2020
DOI: 10.1002/cmdc.202000502
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of Fluorinated Quinoxaline‐Based κ‐Opioid Receptor (KOR) Agonists Designed for PET Studies

Abstract: k-Opioid receptors (KORs) play a predominant role in pain alleviation, itching skin diseases, depression and neurodegenerative disorders such as multiple sclerosis. Therefore, imaging of KOR by a fluorinated PET tracer was envisaged. Two strategies were followed to introduce a F atom into the very potent class of cis,transconfigured perhydroquinoxalines. Whereas the synthesis of fluoroethyltriazole 2 has already been reported, fluoropyrrolidines 14 (1-[2-(3,4-dichlorophenyl)acetyl]-8-[(R)-3-fluoropyrrolidin-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Additional studies have provided further evidence that KOR agonists promote remyelination and recovery in mouse models of MS. Tangherlini et al (2019) synthesised a series of quinoxaline-based KOR agonists and showed that two of these KOR agonists ameliorated EAE paralysis in mice. Tangherlini et al (2020) also observed that treatment with KOR agonists reduced immune cell infiltration into the CNS. They also confirmed that immunomodulatory effects of these compounds depended on the presence of KOR ( Tangherlini et al, 2020 ).…”
Section: Diseases For Which the Kappa-opioid Receptors Has Therapeuti...mentioning
confidence: 75%
See 2 more Smart Citations
“…Additional studies have provided further evidence that KOR agonists promote remyelination and recovery in mouse models of MS. Tangherlini et al (2019) synthesised a series of quinoxaline-based KOR agonists and showed that two of these KOR agonists ameliorated EAE paralysis in mice. Tangherlini et al (2020) also observed that treatment with KOR agonists reduced immune cell infiltration into the CNS. They also confirmed that immunomodulatory effects of these compounds depended on the presence of KOR ( Tangherlini et al, 2020 ).…”
Section: Diseases For Which the Kappa-opioid Receptors Has Therapeuti...mentioning
confidence: 75%
“… Tangherlini et al (2020) also observed that treatment with KOR agonists reduced immune cell infiltration into the CNS. They also confirmed that immunomodulatory effects of these compounds depended on the presence of KOR ( Tangherlini et al, 2020 ). Oral administration of a plant-derived peptide called [T20K]kalata B1 also reduced demyelination and improved functional EAE behavioural scores (level of paralysis) in mice.…”
Section: Diseases For Which the Kappa-opioid Receptors Has Therapeuti...mentioning
confidence: 75%
See 1 more Smart Citation
“…25,26 Thus, characterization of KOR radiopharmaceuticals with antagonism properties and high target specificity is still desirable. 27 A few years ago, we developed KOR radiotracers derived from JDTic [(3R)-7-hydroxy-N-((1S)-1-{[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl}-2-methylpropyl)-1,2,3,4-tetrahydro-3-isoquinolinecarboxamide] established as the most potent and selective KOR antagonist reported so far (Figure 1). 28,29 Among them, the N-…”
mentioning
confidence: 99%
“…Among them, [ 11 C]­GR103545, [ 11 C]­EKAP, and [ 11 C]­LY2795050 have been assessed in clinical trials. [ 11 C]­GR103545 displayed slow binding kinetics and ultrapotency leading to the risk of side effects such as dysphoria, sedation, and psychosis due to its KOR agonist property. , The novel KOR agonist [ 11 C]­EKAP was recently reported to display faster tissue kinetics than [ 11 C]­GR103545 in test–retest reproducibility studies. [ 11 C]­LY2795050, identified as a KOR antagonist with short-term effects, was shown to possess favorable brain uptake, pharmacokinetic properties, and binding profiles but poor stability and moderate KOR selectivity. The analogue [ 11 C]/[ 18 F]­LY2459989 recently evaluated in nonhuman primates was suggested to display a similar in vivo behavior. , Thus, characterization of KOR radiopharmaceuticals with antagonism properties and high target specificity is still desirable …”
mentioning
confidence: 99%